One-punch man. 25, Drive Knight - ONE, 1986- (Shonen Jump manga., 2023)
"In an underground labyrinth, Puri-Puri Prisoner encounters Garo, who is now stronger than ever! Meanwhile, Saitama teams up with the hero Flash while both are lost underground. On the surface, Nyaan toys with Class-A heroes until Drive Knight appears!"--Back cover.